Identification and characterization of differentially expressed lncRNA in 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced cleft palate. (May 2020) - Gao, L-Y; Hao, X-L; Zhang, L; Wan, T; Liu, J-Y; Cao, J
2, 3, 7, 8-Tetrachlorodibenzo- p -dioxin (TCDD) is a ubiquitous environmental pollutant and also a strong teratogen for cleft palate (CP). But up to now, the underlying molecular mechanisms of TCDD-induced CP are largely unknown. More recently, accumulating evidences are revealing important roles of long noncoding RNAs (lncRNAs) in all kinds of diseases including CP. However, the role and molecular mechanism of lncRNAs in TCDD-induced CP are still largely unexplored. Thus, identification of differentially expressed lncRNA (DEL) might help figuring out the mechanism of CP induced by TCDD. In this study, a CP offspring model of C57BL/6 female mice was generated by TCDD (64 µg/kg body weight) induce on embryo day 10 (E10). The incidence rate of CP was 100% in the TCDD group (105) after cervical dislocation on E16. Then, the high-throughput RNA sequencing (RNA-seq) was established to search a comprehensive profile of the lncRNAs. In addition, a coexpression network of lncRNA and messenger RNA (mRNA) was performed to discern potential mechanism. The result showed that 26, 246 novel lncRNAs and 9635 known lncRNAs were screened out, and 413 lncRNA transcripts and 65 mRNA transcripts were identified as being significantly different between the CP group and control group. Notably, we found that there are seven lncRNAs that can target Smad1 and Smad5, which are key molecules of bone morphogenetic protein (BMP) signaling pathway, which suggested that they may be concerned with BMP signaling in TCDD-induced CP. In addition, some lncRNAs targeted the important molecules of Hippo and Wnt signaling pathways. These results suggested that characteristic lncRNA alterations may play a critical role in TCDD-induced CP, which provided a theoretical basis for further research.